The candy smash - Davies, Jacqueline, 1962- (Davies, Jacqueline, 1962- Lemonade war series, 2013)
When candy hearts begin appearing on students' desks, Jessie resolves to get to the bottom of the mystery no matter what the cost. Evan, meanwhile, would rather some secrets stay buried -- especially when they pertain to him.